(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
This article moves beyond theoretical literacy concepts to explore the practical, actionable strategies that proficient readers use to navigate a torrent of text. We will delve into how to set a purpose for reading, which dictates whether you skim, scan, or read closely. We will examine the power of annotation and note-taking to engage with and own the material. Crucially, we will address strategies for synthesizing information from multiple, often conflicting sources, and for practicing critical evaluation to assess an author’s bias, evidence, and reliability. Ultimately, real-world reading is about reclaiming agency over information. It is about moving from passive consumption to active dialogue with a text, equipping ourselves to solve problems, make decisions, and build knowledge. In the following sections, we will unpack this essential toolkit, providing a guide to not just read, but to read with clarity, purpose, and power in the real world.